4 × 32-Gbps Block-Wise QPSK 1200-km SSMF Direct Detection Transmission Based on Delta-Sigma Virtual Carrier Generation - Zhuo Chen; Ziqiang Wu; Jiaqi Huang; Shenmao Zhang; Xueyuan Ao; Zhongzhong Wang; Junxiang Ke; Lilin Yi; Qi Yang (IEEE Photonics Journal)
Direct detection (DD) is one of the most attractive solutions for short and medium reach optical fiber transmission in comprehensive consideration of digital signal processing (DSP), power consumption, and cost. Various single side band (SSB) DD techniques have been widely investigated to detect and process the complex signal. In this paper, we propose a novel approach which uses only high-speed digital input/outputs (IO) to generate both quadrature phase shift keying (QPSK) signal and virtual carrier signal. A transmission of 4 × 32 Gb/s QPSK signal over 1200-km standard single mode fiber (SSMF) in block-wise manner has been successfully demonstrated. Only a single polarization in-phase-and-quadrature (IQ) modulator and one single photodiode (PD) are used for each channel. Compared with conventional DSP of coherent detection, the DSP in the proposed scheme is also simplified that only fixed frequency compensation is required without additional phase noise elimination. The overall system complexity has been greatly reduced.